Al2O3 buffer-facilitated epitaxial growth of high-quality ZnO/ZnS core/shell nanorod arrays. Issue 26 (28th June 2021) - Ru, Fan; Xia, Jing; Li, Xuanze; Wang, Yifan; Hua, Ze; Shao, Ruiwen; Wang, Xuecong; Lee, Chun-Sing; Meng, Xiang-Min
Abstract : II–VI semiconductor heterojunctions show huge potential for application in nanodevice fabrication due to their type-II alignments owing to the better spatial separation of electrons and holes. Abstract : II–VI semiconductor heterojunctions show huge potential for application in nanodevice fabrication due to their type-II alignments owing to the better spatial separation of electrons and holes. However, the hetero-epitaxial growth of high-quality heterostructures is still a challenge, especially for materials with large lattice mismatch. In this work, well-aligned single-crystalline ZnO/ZnS core/shell nanorod arrays were obtained by introducing an Al2 O3 buffer layer. It is interesting that the nature of the ZnS layer varies with the thickness of the Al2 O3 layer. When Al2 O3 is less than 2 nm, the interaction between the substrate and epilayer is strong enough to penetrate through the buffer layer, enabling the growth of ZnS on Al2 O3 -coated ZnO nanorod arrays. On the basis of detailed characterization, a rational growth mechanism of the core/shell heterostructure is proposed, in which the Al2 O3 interlayer can eliminate voids due to the Kirkendall effect around the interface and accommodate a misfit dislocation between the inner ZnO and outer ZnS, resulting in more sufficient strain relaxation in the epitaxy. In addition, cathodoluminescence measurements demonstrate that the optical properties of the ZnO/ZnS heterostructure could be effectively improved by taking advantage of the thin Al2 O3 . The I – V curves characterized by PeakForce tunneling atomic force microscopy reveal that the heterostructure shows a typical rectifying behavior and good photoresponse to ultraviolet light. These findings may provide a reasonable and effective strategy for the growth of highly lattice-mismatched heterostructure arrays buffered by the Al2 O3 layer, broadening the options for fabricating heterojunctions and promoting their applications in optoelectronic devices.